2001
DOI: 10.1034/j.1600-065x.2001.1810107.x
|View full text |Cite
|
Sign up to set email alerts
|

Ly49 and CD94/NKG2: developmentally regulated expression and evolution

Abstract: Murine natural killer (NK) cells express two families of MHC class I-specific receptors, namely the Ly49 family and CD94/NKG2 heterodimers. Stochastic co-expression of these receptors generates diverse receptor repertoires in adult NK-cell populations, whereas fetal NK cells have much more limited receptor diversity as they mostly express CD94/NKG2A but not Ly49. These receptors are also expressed on CD8-T cells and NK1.1+ T cells and regulate their functions, but their expression pattern on NK cells is signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
52
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 1 publication
2
52
1
Order By: Relevance
“…It is well established that some Ly49 family members having an ITIM associate with Src homology 2 domain-containing tyrosine phosphatases such as SHP-1 and SHP-2 (7,8). To examine whether Ly49Q could engage phosphatases in the cytoplasmic ITIM, COS7 cells were transfected with either FLAG-tagged Ly49Q WT cDNA or Ly49Q YF mutant cDNA in which the tyrosine residue in the ITIM was substituted to phenylalanine.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is well established that some Ly49 family members having an ITIM associate with Src homology 2 domain-containing tyrosine phosphatases such as SHP-1 and SHP-2 (7,8). To examine whether Ly49Q could engage phosphatases in the cytoplasmic ITIM, COS7 cells were transfected with either FLAG-tagged Ly49Q WT cDNA or Ly49Q YF mutant cDNA in which the tyrosine residue in the ITIM was substituted to phenylalanine.…”
Section: Resultsmentioning
confidence: 99%
“…It has been postulated that recognition of MHC class I, or related molecules, on target cells by inhibitory NK receptors allows NK cells to prevent self-killing but destroy inappropriate cells possessing decreased levels of MHC class I (4-6). In mice, two types of inhibitory receptors on NK cells have been identified that belong to the Ly49 family and CD94͞NKG2 family (7)(8)(9).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…3 Recent reports suggest that the self-recognizing NK-cell receptor repertoire is built in successive fashion following contact of NK-cell precursors with environmental class I MHC molecules during development. 3,4 However, many questions remain about the origin and lifespans of NK cells. Although still incomplete, a differentiation sequence is emerging that will eventually describe how hematopoietic stem cells generate NK cells in mice and humans.…”
Section: Introductionmentioning
confidence: 99%
“…Some additional NK molecules have been suggested to function as activating receptors. 3 Recent reports suggest that the self-recognizing NK-cell receptor repertoire is built in successive fashion following contact of NK-cell precursors with environmental class I MHC molecules during development. 3,4 However, many questions remain about the origin and lifespans of NK cells.…”
Section: Introductionmentioning
confidence: 99%